The Daily Tail, 11 May 2017 - International Livestock Research Institute (International Livestock Research Institute, 2017)
Newsletter produced for day 4 of the 7th Multi-Stakeholder Partnership (MSP) meeting of the Global Agenda for Sustainable Livestock, achieving multiple benefits through livestock-based solutions, May 2017